2008
DOI: 10.1007/s00383-008-2116-x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol attenuates inflammation and stricture formation in experimental caustic esophageal burns

Abstract: The purpose of medical treatment in the caustic esophageal burns (CEB) is to decrease inflammatory reaction and to prevent stricture formation. Resveratrol has anti-inflammatory and antifibrotic properties. The aim of this study is to investigate potential therapeutic effects of resveratrol in experimental CEB. We divided 42 male Wistar albino rats into five groups: a control group, caustic groups 4 and 28 (esophageal burns were created), and resveratrol groups 4 and 28 (esophageal burns were created and resve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…The latter suggests that the anti-fibrotic and anti-apoptotic effects of OLM administration in esophageal caustic burn observed in our study could be also attributed to the suppression of oxidative stress by AT1R antagonism. This hypothesis is in agreement with the results of previous studies which demonstrated partially successful treatment of caustic esophageal burns by increasing the antioxidant capacity of the tissue [25][26][27][28][29][30][31][32][33][34][35]. The present study provides new evidence that the renin-angiotensin system can be a promising target for the treatment of esophageal burns caused by corrosive agents.…”
Section: Discussionsupporting
confidence: 93%
“…The latter suggests that the anti-fibrotic and anti-apoptotic effects of OLM administration in esophageal caustic burn observed in our study could be also attributed to the suppression of oxidative stress by AT1R antagonism. This hypothesis is in agreement with the results of previous studies which demonstrated partially successful treatment of caustic esophageal burns by increasing the antioxidant capacity of the tissue [25][26][27][28][29][30][31][32][33][34][35]. The present study provides new evidence that the renin-angiotensin system can be a promising target for the treatment of esophageal burns caused by corrosive agents.…”
Section: Discussionsupporting
confidence: 93%
“…Its reliable and extensive antiinflammatory activity has attracted increasing clinical attention [11][12][13][14][15][16][17]. Previous studies demonstrated that its anti-inflammatory effect could be exploited for the treatment of esophageal burns [18], acute small intestinal inflammation [19], colitis [20,21], and many other inflammatory diseases [11,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…There is no universally accepted medical treatment to avoid esophageal stricture formation [1,3,4]. Research has focused on the healing of the burned esophagus and reduction in collagen formation [9,10]. In animal experiments, a variety of different medications, such as erythropoietin, caffeic acid phenethyl ester, mitomycin C, ketotifen, and resveratrol have been used in attempt to prevent esophageal stricture formation after caustic ingestion [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Research has focused on the healing of the burned esophagus and reduction in collagen formation [9,10]. In animal experiments, a variety of different medications, such as erythropoietin, caffeic acid phenethyl ester, mitomycin C, ketotifen, and resveratrol have been used in attempt to prevent esophageal stricture formation after caustic ingestion [6][7][8][9][10]. We investigated the role of dexpanthenol and Y-27632, two different agents with different modes of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation